2016
DOI: 10.1038/srep34644
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of ferulic acid to vanillin in the packed bed-stirred fermentors

Abstract: We performed the biotransformation of ferulic acid to vanillin using Bacillus subtilis (B. subtilis) in the stirring packed-bed reactors filled with carbon fiber textiles (CFT). Scanning electron microscope (SEM), HPLC, qRT-PCR and ATP assay indicated that vanillin biotransformation is tightly related to cell growth, cellar activity and the extent of biofilm formation. The biotransformation was affected by hydraulic retention time (HRT), temperature, initial pH, stirring speed and ferulic acid concentration, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…Food and agricultural wastes are produced in large amounts and are rich in carbohydrates as well as other nutrients and thus can be used efficiently as substrate for the production of bulk chemicals, flavors per se under solid-state fermentation conditions. In addition to the supply of nutrients to the microbial cells, solid substrate also provides an anchorage site for the cells (Yan et al, 2016). The work of various researchers that have used food and agroresidues for microbial production of flavor compounds is summarized in Table 1.…”
Section: Microbial Fermentation Of Agroresidues For the Production Ofmentioning
confidence: 99%
“…Food and agricultural wastes are produced in large amounts and are rich in carbohydrates as well as other nutrients and thus can be used efficiently as substrate for the production of bulk chemicals, flavors per se under solid-state fermentation conditions. In addition to the supply of nutrients to the microbial cells, solid substrate also provides an anchorage site for the cells (Yan et al, 2016). The work of various researchers that have used food and agroresidues for microbial production of flavor compounds is summarized in Table 1.…”
Section: Microbial Fermentation Of Agroresidues For the Production Ofmentioning
confidence: 99%
“…Previous study reported that 2methoxy-4-vinylphenol could be formed by thermal decarboxylation of ferulic acid (Di Gioia et al, 2009), which could be further converted into vanillin. The convention of ferulic acid to 2-methoxy-4-vinylphenol and vanillin could relieve the bitterness of ferulic acid, but decrease the antioxidant activity (Yan et al, 2016). The ketones of 3-hydroxy-2-butanone was disappeared in the soaking pretreated samples after the roasting process, possibly because of its low boiling point of 147.8°C (Pubchem.ncbi.nlm.nih.gov, 2019).…”
Section: Effect Of Processing On Phenolic Compounds and Antioxidant Amentioning
confidence: 99%
“… 12 In another report, Bacillus subtilis could obtain 60.43% molar yield of vanillin in 20–30 h of incubation when initial concentration was 1.5 g L –1 of ferulic acid. 16 The biodegradation of ferulic acid involving bacteria has been widely reported with efficient yield. However, biodegradation of ferulic acid by fungi has been underexplored when compared to the studies related to bacteria.…”
Section: Introductionmentioning
confidence: 99%